The Moderation Effect of Self-Enhancement on the Group-Reference Effect - Xia, Ruixue; Su, Wanru; Wang, Fangping; Li, Shifeng; Zhou, Aibao; Lyu, Dong (Frontiers in Psychology, 2019)
Previous studies have documented that people tend to respond faster to in-group stimuli and memorize in-group traits better. This process of superiority is called the group-reference effect. It may be particularly manifest for ethnic minorities, due to their salient ethnic identity. According to self-enhancement theory, individuals may show preference for positive traits rather than negative traits. However, few studies have explored how the valence of traits may modulate this in-group preference effect. The present study examined how ethnic identity salience and the valence of traits impact on the group-preference effect among 33 Han Chinese in a Tibetan-dominant area and 32 Tibetan participants in a Han-dominant area. Two weeks before the experiment, we tested the ethnic identity salience of participants in the two groups. In the formal experiment, we used the group-reference effect paradigm with three encoding tasks.The results showed that, regardless of whether ethnic identity was salient, both Han Chinese and Tibetan participants made more “yes” responses and fewer “no” responses to the in-group task than to the out-group task. Further, they exhibited faster reaction times to the in-group encoding task in comparison to the out-group encoding task or the font encoding task. both Han Chinese and Tibetan participants had faster RT for in-group positive traits. This suggested that a pervasive processing advantage by group members was present for in-group positive characteristics. The results implied that self- enhancement motivation had a moderation effect on the group-reference effect, and the ethnic identity salience may not be necessary for a group-reference effect